SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL SCREENING OF METAL (II) COMPLEXES DERIVED FROM BENZOFURAN -2-CARBOHYDRAZIDE AND ACETOPHENONE SCHIFF BASE. - M. B. HALLI; RAVINDRA. S. MALIPATIL; R. B. SUMATHI (International Journal of Pharma and Bio Sciences, 2012)
The Cu(II), Co(II), Ni(II), Zn(II), Cd(II) and Hg(II) complexes of the Schiff base derived from reaction between benzofuran-2-carbohydrazide and acetophenone have been synthesized. The synthesized complexes have been characterized on the basis of elemental analysis, conductivity data, magnetic properties, IR and 1H NMR spectral studies. The spectral study shows that Schiff base act as bidentate by coordinating through the azomethine nitrogen and oxygen of the carbonyl groups. Based on these results we have proposed the tentative structure for all of these complexes. The antifungal and antibacterial activities of the ligand and their metal complexes have been screened against fungi Aspergillus niger and Candida albicans and against bacteria Escherichia coli and Staphylococcus aureus.